Specific absorption rate and histopathological evaluation for mobile phone application - Suzanna Harun Ronald (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2015)
This report describes the development of Asian head and hand model using computer-aided design (CAD) software and the analysis of specific absorption rate (SAR) at 900 MHz to 1800 MHz with various hand positions. The motivation for this work has been inspired by the lack of research contributions on the effects of SAR towards Asian users since most work is done using European-sized model. To further contribute for the Asian database, Asian-sized hand models are designed, simulated with a planar inverted-F antenna (PIFA) and investigated for the distribution of SAR with the inclusion of the hand model. The radiation effect at 1800 MHz is tested on Sprague-Dawley rats using histopathology approach.